New generation fiber optic gyroscopes - Hnatenko, O. S.; Levchenko, O.; Morhun, I. (My University, 2024)
The work presents research on the operation of a fiber-optic gyroscope. It consists of the following components: a superluminescent laser diode (wavelength 1550 nm), a circulator, a splitter, a phase modulator, and a 500-meter optical fiber coil (fiber type: Panda). Figure 1 illustrates the operation of this gyroscope [1], which meets the average accuracy metrics of existing analogs.
Keywords: optical fiber; photonic crystal; superluminescent laser